A hybrid forward osmosis/reverse osmosis process for the supply of fertilizing solution from treated wastewater. (December 2019) - Hafiz, Mhd. Ammar; Hawari, Alaa H.; Altaee, Ali
Graphical abstract: Highlights: The engineered fertilizing solution showed average membrane flux of 13.2 LMH. Addition of 0.01 M (NH4 )2 HPO4 reduced reverse solute flux by 36%. In RO, SW30HR membrane should be used for regeneration of the draw solution. Conc. of Cl −, NO3 −, SO4 2- and Na + in the fertilizing solution were within limit. Abstract: This work investigates the application of a hybrid system that combines forward osmosis (FO) and reverse osmosis (RO) processes for the supply of a fertilizing solution that could be used directly for irrigation purposes. In the FO process the feed solution is treated sewage effluent (TSE) and two different types of draw solutions were investigated. The impact of the feed solution and the draw solution flowrates and the membrane orientation on the membrane flux were investigated in the forward osmosis process. RO was used for the regeneration of the draw solution. In the forward osmosis process it was found that the highest membrane flux was 13.2 LMH. The FO process had high rejection rates for total phosphorus and ammonium which were 99% and 97%, respectively. RO achieved 99% total salts rejection rate. Seawater RO (SW30HR) and brackish water RO (BW30LE) membranes were used for the regeneration of the draw solution. The specific power consumption for the regeneration of the draw solution was 2.58 kW h/m 3 and 2.18 kW h/m 3 for SW30HR and BW30LE membranes, respectively. The final product water had high quality in terms of total dissolved solids concentration but the concentration of phosphorus was slightly higher than recommended due to adding 0.1 M of diammonium phosphate in the draw solution.